Natural radioactivity and radon exhalation rate in Brazilian igneous rocks - Moura, C. L. [UNESP]; Artura, A. C. [UNESP]; Bonotto, Daniel Marcos [UNESP]; Guedes, S.; Martinelli, C. D. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
This paper reports the natural radioactivity of Brazilian igneous rocks that are used as dimension stones, following the trend of other studies on the evaluation of the risks to the human health caused by the rocks radioactivity as a consequence of their use as cover indoors. Gamma-ray spectrometry has been utilized to determine the (40)K, (226)K, and (232)Th activity concentrations in 14 rock types collected at different quarries. The following activity concentration range was found: 12.18-251.90 Bq/kg for (226)Ra, 9.55-347.47 Bq/kg for (232)Th and 407.5-1615.0 Bq/kg for (40)K. Such data were used to estimate Ra(eq) H(ex) and I(gamma), which were compared with the threshold limit values recommended in literature. They have been exceeded for Ra(eq) and H(ex) in five samples, where the highest indices corresponded to a rock that suffered a process of ductile-brittle deformation that caused it a microbrecciated shape. The exhalation rate of Rn and daughters has also been determined in slabs consisting of rock pieces similar to 10 cm-long, 5 cm-wide and 3 cm-thick. It ranged from 0.24 to 3.93 Bq/m(2)/h and exhibited significant correlation with eU (=(226)Ra), as expected. The results indicated that most of the studied rocks did not present risk to human health and may be used indoors, even with low ventilation. on the other hand, igneous rocks that yielded indices above the threshold limit values recommended in literature may be used outdoors without any restriction or indoors with ample ventilation. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Natural radioactivity; Dimension stones; Granites; Gamma-ray spectroscopy